2009
DOI: 10.1016/j.amjcard.2009.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Remodeling After the Fontan Operation

Abstract: Hemodynamics following Fontan surgery are notable for right atrial (RA) hypertension and dilation. The effect of this stress on atrial cytoarchitecture has not been studied systematically, and may be relevant to arrhythmias and their treatment. Morphologic and histopathologic analysis was performed on RA and left atrial (LA) tissue from post-mortem specimens of Fontan hearts (n = 47) and compared to control samples from young patients with normal atrial hemodynamics (n = 15). Most Fontan specimens were from yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…A recent histopathological study in a predominantly pediatric cohort of Fontan patients who died shortly after surgery (mean, 1.7 years after Fontan surgery), demonstrated that the amount of atrial fibrosis was not significantly different compared to patients with a normal heart. 5 In contrast, electroanatomic mapping data in older Fontan patients (mean, 18 years after Fontan surgery) showed extensive abnormal atrial endocardium (bipolar voltage ≤ 0.5 mV) in those patients with atrial tachyarrhythmias. 6 Stephenson et al recently demonstrated that the prevalence of IART declines in the initial 4-6 years after Fontan surgery but then increases with age irrespective of the type of Fontan operation, with the highest hazard 10 years post-Fontan and beyond.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A recent histopathological study in a predominantly pediatric cohort of Fontan patients who died shortly after surgery (mean, 1.7 years after Fontan surgery), demonstrated that the amount of atrial fibrosis was not significantly different compared to patients with a normal heart. 5 In contrast, electroanatomic mapping data in older Fontan patients (mean, 18 years after Fontan surgery) showed extensive abnormal atrial endocardium (bipolar voltage ≤ 0.5 mV) in those patients with atrial tachyarrhythmias. 6 Stephenson et al recently demonstrated that the prevalence of IART declines in the initial 4-6 years after Fontan surgery but then increases with age irrespective of the type of Fontan operation, with the highest hazard 10 years post-Fontan and beyond.…”
Section: Introductionmentioning
confidence: 92%
“…The contribution of adverse atrial mechano‐electrical remodeling, including right atrial (RA) dilatation, fibrosis, and atrial wall thickening, to the pathogenesis of IART is less clear. A recent histopathological study in a predominantly pediatric cohort of Fontan patients who died shortly after surgery (mean, 1.7 years after Fontan surgery), demonstrated that the amount of atrial fibrosis was not significantly different compared to patients with a normal heart 5 . In contrast, electroanatomic mapping data in older Fontan patients (mean, 18 years after Fontan surgery) showed extensive abnormal atrial endocardium (bipolar voltage ≤ 0.5 mV) in those patients with atrial tachyarrhythmias 6 .…”
Section: Introductionmentioning
confidence: 98%
“…Evidence from pathological studies suggests that the thickness of the atrial myocardium changes with age as well as a variety of pathological conditions [60][61][62]. Myocyte hypertrophy is seen in animal models used to study AF [63].…”
Section: Atrial Wall Thickness Measurementmentioning
confidence: 97%
“…This speculation is supported by a histopathologic report of atrial remodeling after Fontan procedures; the wall thickness for both the RA and LA was greater than that in the control hearts, and neither the wall thickness nor fibrosis varied with the underlying heart defects or type of Fontan connection. 24 …”
Section: Clinical Course Of the Svtsmentioning
confidence: 99%